Investigation and Research on the Transformation of Thermal Power Generation under the Dual Carbon Background - Zhang, Wenhui; Liu, Chunying; Liu, Jingting; Yan, Anan; Shi, Xiuting; Zhou, Zejiong (International Journal of Natural Resources and Environmental Studies, 2023)
Based on China's energy structure, this work combines the emerging liquid air energy storage technology with the traditional thermal power generation technology to construct a steam-liquid air integrated energy supply system, realizing the integration and development of new energy and traditional technology. The energy supply system mainly uses surplus energy to drive the compressor to compress, cool and liquefy the air and then inject it into the low-temperature storage tank for storage, and a part of the electricity consumed in the liquefaction process is converted into low-temperature cold energy for storage. The heat energy generated by the compression process can be supplied to heat users. The stored cryogenic energy can be used to cool the circulating mass of the power plant, lowering the condensation temperature and improving efficiency. The system is also highly flexible in terms of peak shaving and valley filling under different conditions and with different operating modes to meet different energy supply requirements. At the same time, the system can be combined with various energy supply methods (wind, solar, etc.) to further improve its energy efficiency and economy, implementing the concept of distributed energy utilization.